Classification of aplasia cutis congenita: a 25‐year review of cases presenting to a tertiary paediatric dermatology department. (1st December 2020) - Sathishkumar, D.; Ogboli, M.; Moss, C.
Abstract: Background: Aplasia cutis congenita (ACC) is a rare, congenital disorder characterized by localized or widespread absence of skin at birth with heterogeneous clinical presentation. The classification proposed by Frieden in 1986 is widely used. Aim: To establish whether, 34 years on, the Frieden classification still meets the needs of dermatologists. Methods: We conducted a retrospective chart review of all patients with a diagnosis of ACC presenting over a 25‐year period to a tertiary paediatric dermatology department. We compiled demographic data, clinical characteristics (e.g. number, location and morphology of the lesions), imaging and genetic results where available, and other associated abnormalities, and grouped them according to the Frieden classification. For Type 6 ACC (Bart syndrome) we reviewed neonatal photographs of all babies born with epidermolysis bullosa (EB) over 5 years. Results: Excluding Type 6, there were 56 children with ACC. The scalp was involved in 82.1%, and Type 1 was the commonest type. Over 5 years, 13 of 108 neonates (12%) with EB were born with the appearance of Type 6 ACC. Two children did not fit Frieden's original classification and one had a previously undescribed association of ACC with cleft lip/palate‐ectodermal dysplasia 1 syndrome. Conclusion: We conclude that the Frieden classification remains valid with some modifications. Type 3 ACC probably represents a mosaic RASopathy syndrome, while Type 7 could cover nongenetic ACC attributable to trauma. Type 8 should be subdivided into two subgroups: teratogenic and infective. Type 9 covers at least four subgroups. The classification will continue to evolve as new genes and pathomechanisms emerge.